If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -2x + 7a + -1x = 0 Reorder the terms: 4a + 7a + -2x + -1x = 0 Combine like terms: 4a + 7a = 11a 11a + -2x + -1x = 0 Combine like terms: -2x + -1x = -3x 11a + -3x = 0 Solving 11a + -3x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3x' to each side of the equation. 11a + -3x + 3x = 0 + 3x Combine like terms: -3x + 3x = 0 11a + 0 = 0 + 3x 11a = 0 + 3x Remove the zero: 11a = 3x Divide each side by '11'. a = 0.2727272727x Simplifying a = 0.2727272727x
| 2y=-13(x-5) | | 2x-3y+x-4y= | | 3x-5y-(-3x)= | | 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 |